2019
DOI: 10.1159/000500906
|View full text |Cite
|
Sign up to set email alerts
|

Improving Diagnostic Yield of Capsule Endoscopy in Coeliac Disease: Can Flexible Spectral Imaging Colour Enhancement Play a Role?

Abstract: Introduction: Flexible spectral imaging colour enhancement (FICE) is a form of virtual chromoendoscopy that is incorporated in the capsule reading software and that can be used by reviewers to enhance the delineation of lesions in the small bowel. This has been shown to be useful in the detection of pigmented (ulcers, angioectasias) lesions. However, its application to coeliac disease (CD) images from small bowel capsule endoscopies (SBCEs) has rarely been studied. Methods: This was a European, multicentre stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…With FICE 3, improvement of the delineation was achieved for 46.2% of the angioectasias, 24.5% of the ulcers/erosions, and no cases of villous edema/atrophy. Chetcuti Zammit et al [43] reported that FICE was not useful compared with conventional WLI for the delineation of mucosal changes related to celiac disease. In their study, five expert reviewers evaluated several normal and abnormal CE images obtained from the patients with celiac disease to determine whether the use of FICE can improve the detection of celiac disease-related changes.…”
Section: Characterization Of Lesionsmentioning
confidence: 99%
“…With FICE 3, improvement of the delineation was achieved for 46.2% of the angioectasias, 24.5% of the ulcers/erosions, and no cases of villous edema/atrophy. Chetcuti Zammit et al [43] reported that FICE was not useful compared with conventional WLI for the delineation of mucosal changes related to celiac disease. In their study, five expert reviewers evaluated several normal and abnormal CE images obtained from the patients with celiac disease to determine whether the use of FICE can improve the detection of celiac disease-related changes.…”
Section: Characterization Of Lesionsmentioning
confidence: 99%
“…からもわかるように,ヒトの視覚は波長700 nm 以 上の光に対する感度が無い.そこで700 nm 上を赤外領域 と呼び,近赤外域(波長700 nm 2.5 mm) ,中赤外域(2.5 mm 10 mm) ,遠赤外域(10 mm 1 mm)に分類する.ただ Tm, Yb から445 nm と810 nm の発光を得,Y 2 O 3 : Er, Yb からは660 nm と 1530 nm の発光を得ると同時に,CL によっても両者から それぞれ445 nm と660 nm の発光を得たことを報告して いる 31) .また,山中らは1550 nm の励起下で NaYF 4 : Er, Yb から550 nm と660 nm の発光を得ており,2 光子励起 によらずとも,通常の CW レーザーで深部にある組織の 可視化ができると述べている 32) 次除菌を行う.除菌に成功すれば 13 CO 2 が生成さ れないため,呼気中の 13 CO 2 と 12 CO 2 の比は大気と同じ (1 : 100)である.したがって呼気中の 13 CO 2 と 12 CO 2…”
unclassified